Photoconductive Solution Processed ZnO Quasi-superlattice Films. (8th September 2020) - Buckley, Darragh; Inguva, Saikumar; McNulty, David; Zubialevich, Vitaly Z.; Parbrook, Peter; Gity, Farzan; Hurley, P. K.; O'Dwyer, Colm
Abstract : Photoconductance is reported from single layer and 20 layer quasi-superlattice films of ZnO grown by solution processing and spin coating. At sub-band (532 nm) excitation, significant and stable photoconducrrent is observed and can be modulted by laser power density.